A vital option for food security and greenhouse gases mitigation: planting elite super rice in double- to single-rice cropping fields in China. (2nd September 2021) - Fan, Dongli; Fan, Yidan; Tian, Zhan; Li, Xiubin; Jiang, Min; Sun, Laixiang; Zhong, Honglin; Wang, Kai; Wang, Xiangyi; Jiang, Luguang
Abstract: Double-rice cropping (DRC) in southern China has made outstanding contributions to ensuring food security, along with a large amount of greenhouse gas (GHG) emissions. The observed significant shift from double- to single-rice (DtS) cropping since 1990 in southern China has led to great concerns on food security, despite its contribution to GHG emissions reduction. How to ensure food security without compromising the goal of mitigating GHG emission requires innovative thinking and a comprehensive tradeoff analysis of all plausible options. This study adopts a multi-model coupling method to simulate the yield and GHG emissions trade-offs across grid-cells by incorporating the option of planting elite super rice in the DtS areas. The simulation results indicate that planting elite super rice with longer growth period in the DtS areas has the potential to compensate the annual yield loss caused by the DtS shift while significantly mitigating GHG emissions in comparison with the conventional DRC. In more detail, while the yield and GHG emissions of prevailing single-rice cropping are 48% (±2%) and 54% (±4%) lower than the corresponding (two-season sums) figures of conventional DRC under the current irrigation practice of midseason drainage, the yield and GHG emissions of super rice are 15% (±4%) and 44% (±6%) lower than the above reference figures if the emerging irrigation regime of alternate wetting and drying is adopted. Furthermore, our modeling simulations demonstrate the feasibility of promoting elite super rice cultivars across southern China. The research suggests a viable option for China to balance the trade-off between food security and GHG mitigation.